Group Mentoring: a Way to Retain ´High-Risk´ Teachers on the Job - Lisbeth Lunde Frederiksen (European Teacher Education Network, 2015)
The present article concerns group mentoring combined with action learning as a way to counteract work related sickness and early retirement for´ high risk´ teachers. Focus has been on reflection and vitalization. The data shows that this way of working has many possibilities in supporting and developing ´high risk´ teachers. Changes concerning reflection and vitalization were made and developed further by means of exploratory dialogues, in combination with actions, and in exercise reflections on learning in practice. Numerous statements in logbooks and interviews related to the project show signs of reflections, experiences of a changed and better practice, and feelings of vitalization. The question is whether all participants will be able to continue reflections after the end of the course.